Forest fragmentation reduces local diversity but maintains regional diversity by increasing compositional turnover in the Humid Chaco herpetofauna - Leonardo D. Aguiar; Martín A. Ortiz; Laura C. Pereyra; Diego Nuñez; Alejandro R. Giraudo; Eduardo F. Schaefer (Forest Ecology and Management, 2026)

The interplay of geography and urbanization shapes morphological variation in the common toad, Rhinella arenarum - Laura C. Pereyra; Mario R. Ruiz-Monachesi; Rebeca Acosta; Dionel Aguiar; Clarisa L. Bionda; Ana G. Boggio; Rocío P. Demartín; Romina Ghirardi; Pablo R. Grenat; Javier A. López; Guillermo Natale; Lorena B. Quiroga; et al. (Urban Ecosystems, 2026)

The Earth’s magma ocean: Processes and current interpretations from an interdisciplinary perspective - Charles-Édouard Boukaré; Laura K. Schaefer; Hanika Rizo (Physics of the Earth and Planetary Interiors, 2025)

Exploring the transformative effects of calorie restriction on the lacrimal gland in adult mice - Olivier Mauduit; Prashant Kumar; Kaitlin K. Scholand; Emre Aksan; Laura Schaefer; Anmar Abu-Romman; Vanessa Delcroix; Zhiyuan Yu; Aude I. Sindikubwabo; Ron Korstanje; Helen P. Makarenkova; Cintia S. de Paiva (GeroScience, 2025)
Advanced age is one of the most recognizable risk factors for dry eye. Dry eye disease affects millions worldwide and can result from age-related lacrimal gland dysfunction, which correlates with a decline in lacrimal gland secretory cell function and chronic inflammation. This study investigated the potential of calorie restriction to maintain lacrimal gland and ocular surface health. Adult female C57BL/6 J mice were subjected to a 40% calorie restriction for 4 months, starting at 6–7 months and continuing until 10–11 months. These mice were compared to controls fed ad libitum. Bulk RNA sequencing of lacrimal glands, conjunctiva, and cornea subjected to calorie restriction compared to ad libitum revealed significant differentially expressed genes (DEGs). Pathways enriched in the upregulated DEGs indicate enhanced circadian rhythm, secretory functions, and lipid metabolism. These findings were confirmed using individual qRT-PCR and western blotting. In contrast, pathways enriched in the downregulated DEGs were associated with immune cell activation, adaptive immune responses, extracellular matrix remodeling, and metalloproteinase activity. Histological sections of calorie-restricted lacrimal glands revealed reduced mononuclear cell infiltration and fewer positive cells for CD4, CD19, and MHC II than in ad libitum lacrimal glands. Calorie restriction also prevented age-related corneal barrier dysfunction and mitigated age-related conjunctival goblet cell loss, hallmarks of dry eye disease. These findings suggest that calorie restriction supports lacrimal gland and ocular surface health by reducing inflammation and extracellular matrix remodeling and by enhancing the lacrimal gland’s secretory function.

Ayahuasca Pretreatment Prevents Sepsis-Induced Anxiety-Like Behavior, Neuroinflammation, and Oxidative Stress, and Increases Brain-Derived Neurotrophic Factor - Rick Wilhiam de Camargo; Larissa Joaquim; Richard Simon Machado; Suelen de Souza Ramos; Lara Rodrigues da Rosa; Linério Ribeiro de Novais Junior; Khiany Mathias; Lara Maximiano; Yasmin Ribeiro Strickert; Rafael Nord; Maria Laura Gava; Eduarda Scarpari; et al. (Molecular Neurobiology, 2025)

Aged regulatory T cells fail to control autoimmune lacrimal gland pathogenic CD4+ T cells - Kaitlin K. Scholand; Laura Schaefer; Gowthaman Govindarajan; Zhiyuan Yu; Jeremias G. Galletti; Cintia S. de Paiva (GeroScience, 2025)

Life cycle assessment use in the North American building community: summary of findings from a 2011/2012 survey - Maureen A. Olinzock; Amy E. Landis; Christi L. Saunders; William O. Collinge; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (The International Journal of Life Cycle Assessment, 2015)

Analyzing the Practice of Life Cycle Assessment - Christi L. Saunders; Amy E. Landis; Laurel P. Mecca; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (Journal of Industrial Ecology, 2013)
Summary Life cycle assessment (LCA) is a quantitative tool used to evaluate the environmental impacts of products or processes. With respect to buildings, LCA can be used to evaluate the environmental impacts of an entire building's life cycle. Currently LCA in the building area is used in a limited capacity, primarily to select building products. In order to determine the causality for the lack of whole‐building LCAs, focus groups with members of the architecture, engineering, and construction (AEC) communities were held. This article investigates the current level of knowledge of LCA in the AEC community and then discusses the benefits and barriers to the practice of LCA. In summary, the goal of the research was to identify why LCA is not used to its fullest potential in a whole‐building LCA. In an open forum and moderated setting, focus group participants were asked individually to self‐identify their experience with LCA, a brief education session on LCA was held, and then benefits and barriers to LCA were discussed. The focus group sessions were transcribed and systematically coded by social researchers in order to analyze the results. Hybrid flow and radar charts were developed. From the focus group results, the most important benefit to LCA was “provides information about environmental impacts.” The results did not identify a prominent barrier; however, building‐related metrics were ascertained to be one of the more crucial barriers. The benefits and barriers classified by this analysis will be utilized to develop a subsequent online survey to further understand the LCA and AEC community.

Erratum to: Dynamic life cycle assessment: framework and application to an institutional building - William O. Collinge; Amy E. Landis; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (The International Journal of Life Cycle Assessment, 2013)

Dynamic life cycle assessment: framework and application to an institutional building - William O. Collinge; Amy E. Landis; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (The International Journal of Life Cycle Assessment, 2013)

Coding sequence, chromosomal localization, and expression pattern of Nrf1: the mouse homolog of Drosophila erect wing - Laura Schaefer; Heather Engman; Jeffrey B. Miller (Mammalian Genome, 2000)